A study on prevalence of refractive error and its associated factors among school children in Tamil Nadu - Megala, M.; Dhamodharan, S.; Duraimurugan, M.; Ganapathi, K. Chellavel (International Journal Of Community Medicine And Public Health, 2020)
Background: Refractive error is an avoidable cause of visual impairment. Children do not complain of defective vision. This warrants early detection and treatment. The study was conducted with the objective of estimating the prevalence of refractive error in school children and its associated factors. Methods: This was a cross sectional study conducted in schools of selected district in Tamil Nadu from July 2017 to January 2018. Sample size of 422 covered. A semi structured questionnaire was used to collect the details and also screened for refractive errors. Data was analysed using SPSS. Results: Among the 422 students screened, 86 (20.4%) had refractive error. The prevalence of refractive error showed significant association with age, education and occupation of parents, socio economic status, parental history of refractive error, duration of watching television and body mass index. Conclusions: Refractive errors among school children can be easily identified by regular eye screening programmes, promptly treated can be protected from future complications. Periodic screening of school children is very essential to improve the quality of eye-sight.